2007
DOI: 10.1111/j.1708-8208.2007.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Augmentation Using Sinus Membrane Elevation and Peripheral Venous Blood for Implant‐Supported Rehabilitation of the Atrophic Posterior Maxilla: Case Series

Abstract: The present case series demonstrate that the creation of a secluded space in the maxillary sinus and filling with venous blood results in bone formation at simultaneously installed dental implants over a 6-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 16 publications
9
95
2
1
Order By: Relevance
“…To enhance bone formation in the maxillary sinus floor using sinus membrane elevation, graft materials or techniques that enable the membrane to remain in the elevated position are necessary [7] . The results of Kim et al (2010) [8] study were different from the findings of Hatano et al (2007) [6] , who stated that the mean bone height gained was 10mm 6 months following the procedure. The inconsistency of these results may have resulted from the use of different methods of evaluating endosinus bone gain.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…To enhance bone formation in the maxillary sinus floor using sinus membrane elevation, graft materials or techniques that enable the membrane to remain in the elevated position are necessary [7] . The results of Kim et al (2010) [8] study were different from the findings of Hatano et al (2007) [6] , who stated that the mean bone height gained was 10mm 6 months following the procedure. The inconsistency of these results may have resulted from the use of different methods of evaluating endosinus bone gain.…”
Section: Discussioncontrasting
confidence: 53%
“…Although the mechanisms are not fully understood, it is obvious that the controlled trauma when lifting the sinus membrane results in the formation of a blood clot and subsequent bone formation. The displacement of the membrane probably triggers a series of events, including blood and fibrin clot formation, cellular migration and differentiation, angiogenesis, and osteogenesis [6] . The increased thrombin generation on the surfaces of titanium implants may also stimulate proliferation and inhibit apoptosis of osteoblasts [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hatano et al and Moon et al's study, 21 The insertion of peripheral venous blood as alternative to graft material can be safely used in maxillary sinus augmentation as demonstrated in this chapter.…”
Section: 3mentioning
confidence: 93%
“…[15][16][17] However some studies reported new bone formation in animal and human's sinus with membrane elevation alone, resorbable gelatin sponge alone, venous blood alone and autologous fibrin gel with concentrated growth factors alone as alternatives to bone materials. [18][19][20][21][22][23][24][25] According to these studies, bone substitutes may not be a prerequisite for sinus augmentation. The function of elevated sinus membrane is controversial, but some studies reported that sinus membrane acted as periosteum and showed osteoinductive potetnial.…”
Section: Sinus Augmentation Using Lateral Window Approachmentioning
confidence: 99%